Empowering academics to be adaptive with eLearning technologies: An exploratory case study - Flavell, Helen; Harris, Courtenay; Price, C.; Logan, E.; Peterson, S. (2019)
© 2019. This paper describes an exploratory case study investigating the capacity of a multidisciplinary approach to academic development, to empower adaptive responses to ongoing technological change impacting on teaching practice. A quasi-experimental design with an intervention group (n = 22) and a comparative control group (n = 7) was adopted. Pre and post online questionnaires were administered to participants in both groups to evaluate attitudes and experiences relating to technology use in teaching and learning. The questionnaires were adapted from the Technology Acceptance Model. Qualitative measurement of the intervention group's experiences following the professional development was captured using semi-structured interviews, followed by two focus groups to confirm the interview findings. Results indicate that the professional development impacted positively on participants through significantly increased levels of confidence and perceived ease of use. Qualitative data indicated participants experienced cognitive, emotional, and/or practical changes during and/or following the professional development.